1994
DOI: 10.1007/bf01400649
|View full text |Cite
|
Sign up to set email alerts
|

Development of the neurocranium after transsutural fixing by new, resorbable poly-L-lactide miniplates. a comparison to fixing with the common titanium miniplates

Abstract: The right coronal sutures of twelve (12) newborn rabbits were fixed with commercially available, self-reinforced poly-L-lactide miniplates, with eight (8) rabbits sham treated with titanium miniplate fixation as reference experiments, in order to demonstrate the possible effects on skull growth. After six (6) months follow-up, both types of plate were detected to have caused a similar asymmetry in the neurocranium. Therefore, in our opinion, fixing across growing sutures, even with the new biodegradable device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This continuous decrease in integrity could anyway be positive in some applications, e.g. in bioabsorbable devices for cranial growth in children (Antikainen et al ., ), where compensatory bone lengthening (normalizing bone response) may take place, leading to a maintained overall skeletal morphology (Eppley and Sadove, ). For these purposes, more rapidly degrading materials, such as PLGA, are preferred because they soften with time and allow for device elongation without interfering with bone regrowth (Eppley and Sadove, ).…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…This continuous decrease in integrity could anyway be positive in some applications, e.g. in bioabsorbable devices for cranial growth in children (Antikainen et al ., ), where compensatory bone lengthening (normalizing bone response) may take place, leading to a maintained overall skeletal morphology (Eppley and Sadove, ). For these purposes, more rapidly degrading materials, such as PLGA, are preferred because they soften with time and allow for device elongation without interfering with bone regrowth (Eppley and Sadove, ).…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…It avoids the unwanted effects of metallic implants in the skull [13] as it does not interfere with modern neuro-imaging. The results of careful experimental studies have shown that fixation with thin self-reinforced poly-L-lactide (SR-PLLA), like poly-L-lactide (PLLA) miniplates can be achieved in the cranium without any adverse effects such as delayed union or inflammatory or clinically manifested foreign-body reactions [1,7,8,9]. Successful clinical results were reported by Fuente del Campo et al [3], who operated on 32 patients, fixing their maxillary osteotomies with SR-PLLA plates.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 8 9 ] However, in certain newborn rabbits, it was identified that placing even resorbable hardware could cause local asymmetry during the growth phase, which later was reversible. [ 10 ] All these studies involved critical areas such as coronal, frontal, or sagittal sutures. There are very less human studies in this aspect.…”
Section: Discussionmentioning
confidence: 99%